Conventional Mutual Funds Out Perform Islamic Mutual Funds in the Context of Pakistan. A Myth or Reality - Zeeshan, Muhammad; Han, Jiabin; Rehman, Alam; Saleem, Kashif; Shah, Raza Ullah; Ishaque, Amir; Farooq, Naveed; Hussain, Arif (International Journal of Economics and Financial Issues, 2020)
Mutual Funds enable small investors to enjoy the benefits of the capital market instruments with small amount using the expertise of professional managers. This study examines the risk adjusted performance, timing and selection abilities of conventional and Islamic mutual funds in the context of Pakistan. The emergence of Islamic portfolio in the recent years has put mutual fund investors in puzzle, whether to opt for Islamic or conventional funds. The study analyzes 90 (ninety) open ended funds data, which is comprised of 45 each from Islamic and conventional funds, selected randomly over the period of 2011-2019, from the existing population of open-ended mutual funds. We employ asset pricing models i.e. CAPM (1966), and Fama French three factors (1993) model, to measure the risk adjusted performance, and Treynor and Mazuy (1966) model for predicting their selectivity and timing abilities. The results demonstrate that Conventional funds perform better than Islamic funds in term of risk adjusted performance, and conventional funds predict better market timing and selection abilities than its Islamic portfolio. The study has certain implications for the managers of the assets management companies in selecting their best portfolios, making timely investment and will, also be useful for the investors in knowing funds, which perform better. Keywords: Risk adjusted performance, Market timing and Selection abilities, Open ended mutual fund, Pakistan JEL Classifications: G22, G12 DOI: https://doi.org/10.32479/ijefi.10090